Uroperitoneum after Caesarean Section - Antonakopoulos Nikolaos; Kyritsis Nikolaos; Vlachos Dimitrios; Vlachos Georgios (Hindawi Limited, 2013)
Intraoperative injuries of the bladder and the attendant vesicouterine and vesicovaginal fistulas formation are reported as rare events, but the rapid increase in the number of caesarean sections has contributed to the emergence of these complications. Early recognition of these complications makes them much easier to deal with, while simple measures intraoperatively can ensure that these complications will not escape attention. We present our rare case of uroperitoneum after cesarean section, the way of diagnosis and treatment, and due to this incident we review in detail the existing literature on the topic.